Unpacking resource gains in Portuguese business expatriates: The role of company policies. - Coelho, J. V. (EURAM 2023, 2023)
Current critical matters pertaining to expatriate and global mobility management include the decisions multinational companies (MNCs) must make about assigning someone to an overseas location for a certain period. Aiming to address this sensitive topic, the present article focuses on how job-related resource development dynamics relate with contextual influences as provided by company expatriate policies, considered as resource enabling or qualifying condition, and expatriate willingness to accept international assignments, in MNCs of a less frequently cited and developed country (Portugal). Expatriation company policies and systems are still acknowledged as a major weakness in the global work and mobility management literature. Aiming to expand upon existing knowledge concerning company policies, job-related resource preservation processes and individual willingness to engage with expatriation assignments, the present study considers interaction effects, as proposed by the conservation of resources (COR) theory, as lens to understand if company policies are enacted as qualifying resource passageway of expatriate willingness levels, in developing business contexts. Overall, three profiles of expatriate willingness, linked to different policy orientations, were considered to mirror contrasting employee intentions towards working abroad: conformist expatriates, protean expatriates and disrupted expatriates. For this proposed groupings, different resource process dynamics were observed, ranging from upward resource fluctuation to downward pressure, respectively. Managerial implications are provided to further understand individual-level effects of dynamic, non-functionalist company expatriate policies, in developing companies and economies.